(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2019)
Objective: To survey in the literature the role of the nurse in the care of people with urinary incontinence (UI). Methods: Integrative literature review from the publications within the period of 2013 in the databases: BDENF, LILACS, Web of Science, PubMed and SciELO, in the Portuguese, English and Spanish languages. The sample consisted of 11 publications, most of them in English. Results: The data were categorized into three dimensions of care: educational (three articles), care (eight articles) and management (an article, which was also categorized as care). Educational: although nurses presented superfi cial and incomplete knowledge about incontinence, playful strategies were used for teaching. Assistance: the use of superabsorbent diapers and pads, 3% dimethicone impregnated wipes, spray for the formation of polymer film for incontinence-associated dermatitis, pelvic musculature, urethral massage, bladder training, and eating habits modifi cation were recommended. Gerencial: the quality of nursing care for the elderly with UI was evaluated through protocols, standards and Standard Operational Procedures (SOPs). Conclusion: There is a shortage of studies on the subject and it was evidenced that the nurse assumes an assistance role in urinary incontinence, although its knowledge is incipient.